Theoretical Examination of the Radiation Protecting Properties of CaTiO3 Material Sintered at Different Temperatures - Essia Hannachi; M. I. Sayyed; Suhairul Hashim; Karem Mahmoud; Yassine Slimani (Crystals, 2023)
This research is devoted to studying the radiation-protecting characteristics of calcium titanate (CaTiO3) perovskite-based ceramic material. The ceramics were made by the solid-state reaction method (SSRM) and treated at temperatures of 1300 °C, 1200 °C, and 1100 °C. The structural characteristics of the ceramics were analyzed by XRD and FT-IR. The results indicated a CaTiO3 phase formation with an orthorhombic structure. The size of the crystallites was in the range of 27–36 nm and was found to increase as the temperatures increased. The relative density showed an increase from 93% to 96% as the temperatures varied from 1100 °C to 1300 °C. The impact of temperature on the radiation-protecting characteristics of the CaTiO3 ceramic was assessed using the Monte Carlo simulation (MCS). There was a slight decrease in the γ-photons average track length with a raising of the temperature. At a γ-photon energy of 0.662 MeV, the γ-photons’ average track lengths diminished from 3.52 cm to 3.38 cm by raising the temperature from 1100 °C to 1300 °C. The illustrated decrease in the γ-photons average track length affected the linear attenuation coefficient (µ) where the µ increased from 0.28 to 0.30 cm−1 with a rising temperature from 1100 °C to 1300 °C.